2005
DOI: 10.1001/archderm.141.7.847
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed High-Dose Corticosteroids Combined With Low-Dose Methotrexate in Severe Localized Scleroderma

Abstract: Setting: Dermatology department at a university hospital in Bochum, Germany.Patients: Fifteen patients with histologically confirmed severe LS.Interventions: Oral methotrexate (15 mg/wk) combined with pulsed intravenous methylprednisolone (1000 mg for 3 days monthly) for at least 6 months.Main Outcome Measures: Treatment outcome was evaluated by means of a clinical score, 20-MHz ultrasonography, and histopathologic analysis. Safety assess-ment included the monitoring of adverse effects and clinical laboratory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
115
0
14

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 165 publications
(144 citation statements)
references
References 36 publications
6
115
0
14
Order By: Relevance
“…In our study, MTX was effective in more than two-thirds of patients, and the rate of efficacy was significantly higher than in the placebo group, in which a short course of prednisone was able to control the disease process in fewer than one-third of the patients (P ϭ 0.001). Our findings partially confirm those of previous retrospective studies in children, in which the rate of response to MTX ranged between 71% and 94% (4)(5)(6)(7)(8)27). However, the numbers of patients in those studies were small, the studies were not randomized controlled trials, and the outcome measures were mainly based on the subjective judgment of the physician.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In our study, MTX was effective in more than two-thirds of patients, and the rate of efficacy was significantly higher than in the placebo group, in which a short course of prednisone was able to control the disease process in fewer than one-third of the patients (P ϭ 0.001). Our findings partially confirm those of previous retrospective studies in children, in which the rate of response to MTX ranged between 71% and 94% (4)(5)(6)(7)(8)27). However, the numbers of patients in those studies were small, the studies were not randomized controlled trials, and the outcome measures were mainly based on the subjective judgment of the physician.…”
Section: Discussionsupporting
confidence: 91%
“…The treatment response with definite clinical improvement in both arms of our study corresponds well with outcomes previously reported (4)(5)(6)27). In the only study in which oral corticosteroids (prednisone 0.5-1 mg/kg/day) were used as monotherapy, improvement was shown in most patients, with remission achieved in as many as 23.5% (19).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In children, the current treatment for severe localized scleroderma is a combination of systemic corticosteroids and low-dose methotrexate (5)(6)(7)(8). The management of severe localized scleroderma is challenging, and the detection of disease activity remains a fundamental problem, both in the evaluation of the need for treatment and the assessment of therapeutic efficacy over time.…”
mentioning
confidence: 99%